Answer:
(3, - 4) is the solution to the system of equations.
Step-by-step explanation:
1. Rewrite one of the equations so it eighter starts with y= or it starts with x=
Here the easy way is to write X+y=-1 in the form x=
X= - y - 1
2. Substitute X= - y - 1 in the other equation 5X+3y=3:
5X+3y=3
X= - y - 1
5(- y - 1)+3y=3
-5y -5 +3y = 3
-2y = 3 +5
2y = -8
y = - 4
3. Now substitute this value y = - 4 in X= - y - 1
X= - (y) - 1
y = - 4
X= - (- 4) - 1
X = 4 - 1
X =3
4. So X =3 and y = - 4 gives this coordinate (3, - 4), which is the solution to the system of equations.